SAT0169 RISK OF SERIOUS INFECTIONS IN OFFSPRING ACCORDING TO TNFI SUBTYPES. (June 2019) - Vinet, Evelyne; St-Pierre, Yvan; Moura, Cristiano; Curtis, Jeffrey; Bernatsky, Sasha
Abstract : Background: TNFi subtypes have differential trans-placental passage; infliximab and adalimumab (both monoclonal immunoglobulins) have the highest transfer, reaching higher fetal than maternal blood levels, while certolizumab (a pegylated Fab fragment) and etanercept (a fusion protein) display the lowest passage (less than 0.25% and 4-7% respectively). Thus, some TNFi subtypes could cause immunosuppression in the offspring. However, to date, there is no data on the risk of serious infections according to TNFi subtypes. Objectives: We evaluated serious infections in a large group of children born to mothers with chronic inflammatory diseases who used TNFi during pregnancy. Our comparators were unexposed offspring born to affected and unaffected mothers. We determined if the risk of serious infections differed according to TNFi subtypes. Methods: We identified all women with ≥1 hospitalization for delivery after a diagnosis of rheumatoid arthritis (RA), ankylosing spondylitis (AS), psoriasis (PsO), psoriatic arthritis (PsA), or inflammatory bowel diseases (IBD), and a randomly selected group of unaffected mothers, matched ≥4:1 for age, year of delivery, and state of residence, using MarketScan database (2011-2016). Only women continuously enrolled within MarketScan for ≥12 months prior to delivery and with available child linkage were included. We defined TNFi exposure based on ≥1 filled prescription and/or infusion procedure code during pregnancy and/or the preconception period. We further refined TNFi exposure based on potential for high (infliximab, adalimumab, golimumab) versus low (certolizumab, etanercept) placental transfer. We ascertained serious infections in the offspring based on ≥1 hospitalization with infection as a primary diagnosis, in the first year of life. We performed multivariate analyses, adjusting for maternal demographics, disease type, co-morbidities, pregnancy complications, and drugs (corticosteroids, DMARDs, non-TNFi biologics). Results: We identified 16, 490 offspring of mothers with RA (4, 142), AS (381), PsO/PsA(5, 743), and IBD (6, 731), as well as 164, 553 children born to unaffected matched mothers. Among offspring whose mothers had inflammatory diseases, 1, 611 (9.8%) were exposed to TNFi during pregnancy, 338 (2.0%) were unexposed during pregnancy but exposed in the preconception period, and 14, 541 (88.2%) were unexposed both during the pregnancy and preconception periods. The percent of serious infections in offspring of inflammatory disease mothers with no TNFi exposure (2.1%; 95% CI 1.9, 2.3) was similar to those with TNFi exposure (2.3%; 95% CI 1.6, 3.0), while the percent of serious infections in children born to unaffected mothers was 1.6% (95% CI 1.6, 1.7). In offspring exposed to TNFi with high placental transfer, the percent of serious infections was 2.3% (95% CI 1.6, 3.3), while for TNFi with low transfer, it was 1.7% (95% CI 1.0, 3.1). In multivariate analyses, we did not observe an increased risk of serious infections in TNFi exposed offspring versus unexposed offspring of mothers with inflammatory diseases (OR 1.0; 95% CI 0.7, 1.5). Results were similar when we restricted TNFi exposure to the third trimester (OR 1.1; 95% CI 0.7, 1.7). In multivariate analyses of children exposed to TNFi with high versus low placental transfer, our point estimate was consistent with increased risk, but the confidence interval was wide, including the null value (OR 1.43; 95% CI 0.66, 3.08). Conclusion: When we compared the risk of serious infections in offspring exposed to TNFi with high versus low placental transfer, we observed a potential trend for an increased risk, although the confidence interval was wide and included the null value. Our findings stress the need to further study this issue. Disclosure of Interests: None declared